Studi Tentang Kelelahan Kerja pada Pegawai di Laboratorium Pengujian Teknik Bidang Bina Marga Dina Pupr Provinsi NTT Tahun 2022 - Fatima Dewi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Fatigue has the meaning of a person's body's ability to convey that his body has exceeded the limits of its ability to do work. So there is a need for recovery by resting. The research objective was to find out the description of employee fatigue based on age, gender, workload and employee working hours. The type of research used is quantitative descriptive research. The research population is all employees, namely 68 people with a sampling technique using a total sampling technique, namely taking the entire population to be used as research objects. The results showed that 42 people (61.8%) were tired, 26 people (38.2%) were very tired. Age 15-45 years tired 30 people (31.5%) and very tired 21 people (19.5%), aged 46-64 years tired 12 people (10.5%) and very tired 5 people (6.5%) ). Gender tired men 29 people (30.9%), women 13 people (11.1%), while very tired men 21 people (19.1%) and women 5 people (6.9%) ). The workload is quite good, 14 people (12.4%) are tired, and 6 people (7.6%) are very tired. Good workload 21 people (22.2%) are tired and 15 people (13.8%) are very tired, while employees in the very good workload category 7 people (13.8%) are tired and 5 people are very tired (4.6%) ). Employees with long working hours of 6-8 hours who are tired 19 people (15.4%) are very tired 6 people (9.6%), employees with working hours/day > 8 hours are tired 23 people (26.6%) and 20 people (16.4%) were very tired. The advice given is to make a standard operation of work implementation (SOP) so that employees remain in accordance with work standards so as to create a comfortable working atmosphere to reduce the risk of fatigue due to work.